The Effectiveness of Cooperative Learning Model of NHT Type Assistance in Teaching Materials in Improving Student Learning Outcomes in Social Science Students at State Junior High School 4 Pekanbaru - Hanifah Hanifah; Caska Caska; Sri Kartikowati (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This study aims to determine the effectiveness of the Numbered Head Together (NHT) type of cooperative learning model assisted with teaching materials in improving student learning outcomes in social studies subjects at State Junior High School (SMPN) 4 Pekanbaru. The sampling technique using cluster random sampling techniques, namely class VII.3 as the experimental class, and VII.4 as the control class. Data were analyzed using randomized control group pretest-posttest design through the results of the T Test (Different Test). Based on the results of the study showed the results of pre-test 73.95 and post-test of 85.19 with a difference of 11.24. In the pre-test control class was 73.84 and the post-test results were 79.78 with a difference of 5.94. From the results of this difference can be seen that there is an increase in learning outcomes, especially in the experimental class where there are differences in completeness of learning outcomes between the control class and the experimental class. This is also supported by students' learning attitudes in the experimental class (VII.3) which are categorized as "good" (68%) in the learning process. Whereas in the control class, students have the category "quite good" (45.94%) in being following the learning process. The level of learning effectiveness is 5.30. Overall it can be concluded that the NHT learning model is assisted with effective teaching materials significantly in improving student learning outcomes.